Estimation of Production and Consumption of Particle Board and Medium Density Fibre Board in India during the Year 2019-20 - Upadhyay, V. K. (Indian Forester, 2022)
and Shyam MukundumThe study was carried out to understand the current status of particle board (PB) and medium density fibre (MDF) board industries of India. A survey was conducted covering 49% of particle board industries and 89% of MDF industries in India. The status and trend of particle board and MDF products were analyzed to estimate future demand and consumption of particle board and MDF in India. The estimated production of particle board and MDF during the year 2019-20 is 2.63 million cum and 1.47 million cum respectively. However, consumption of particle board and MDF was 2.91 million cum and 1.68 million cum. The import of particle board and medium density fibre was 0.29 million cum and 0.26 million cum respectively and the export of PB and MDF was 0.01 million cum and 0.03 million cum respectively during the year 2019-20. It is projected that the average annual growth rate (AAGR) of production will be 6.5% for particle board and 6.1% for MDF.